Analisis Pengaruh Stock Split Terhadap Harga Saham, Volume Perdagangan Dan Abnormal Return Pada Perusahaan Yang Tergabung Dalam Lq45 Periode 2017-2019 - Ratnawati Raflis (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
The purpose of this research is to analyze the dif erences of stock price, trading volume activity, and abnormal return before and after stock split event, sothat investors could use this event to gain benefit. The independent variables in this stock price, trading volume activity, and abnormal return, the dependent variable is stock split . The study population was companies listed on the LQ45 in 2017-2019. The sample selection using purposive sampling method and obtained a total sample of 4 companies. Hypothesis testing uses two def erence test means. Data analysis using the IBM SPSS Statistics 21 application. The results showed that stock price had no ef ect on stock split with a significance value of 0.156 > 0.05, trading volume activity had no ef ect on stock split with a significance value of 0.806 > 0.05, and abnormal return had no ef ect on stock split with a significance value of 0,263 > 0,05.